How to Enhance the Health Education Capabilities of Optometry Interns in Myopia Prevention and Control During Clinical Practice - Zhao, Bingxin; Li, Xiuhong (Journal of Research in Vocational Education, 2025)
Optometry interns demonstrate deficiencies in health education regarding myopia prevention and control when interacting with myopia patients and their families during clinical practice. These shortcomings are primarily reflected in three aspects: inadequate understanding of the significance of myopia prevention and control, incomplete coverage of educational content, and poor competency in addressing complex cases. In response to these issues, this paper systematically elaborates on the clinical implications of myopia prevention and control, comprehensively summarizes key educational components and critical considerations, and proposes innovative practical training methods. These methods incorporate simulated teaching exercises and real-case participation, aiming to substantially improve optometry interns' health education competencies in myopia prevention and control within clinical settings.